A new type of calcium-rich biochars derived from spent mushroom substrates and their efficient adsorption properties for cationic dyes - Zhang, Haibo; Su, Long; Cheng, Caiping; Cheng, Hongyan; Chang, Mingchang; Liu, Fenwu; Liu, Na; Oh, Kokyo (Frontiers in Bioengineering and Biotechnology, 2022)
This study evaluated the potential application of calcium-rich biochars (GSBC and LSBC) derived from spent mushroom substrates (Ganoderma lucidum and Lentinus edodes). The effects of pyrolysis temperature on the calcium-rich biochars characteristics and their adsorption mechanism for cationic dyes (Malachite Green oxalate (MG) and Safranine T (ST)) were studied systematically. The increase in pyrolysis temperature from 350 to 750 ℃ led to an increase in both biochar ash, Ca content, and specific surface area, which made high-temperature biochars (GS750 and LS750) the superior adsorbents for cationic dyes. Batch adsorption results showed LS750 was more efficient to adsorb dyes than GS750 attributed to its higher Ca content and larger specific surface area. According to the Langmuir model, LS750 had high adsorption capacities of 9388.04 and 3871.48 mg g-1 for MG and ST, respectively. The adsorption mechanism of dye MG could be attributed to pore filling, hydrogen bonding, electrostatic interaction, ion exchange, and π-π stacking, while ST adsorption mainly involved pore filling, electrostatic interaction, ion exchange, and π-π stacking. Attributed to their excellent adsorption performance, cheap source, and good reusability, biochars obtained from SMSs were very promising in dyeing wastewater treatment.